AgI‐Promoted Cascade for Difluoromethylation of Activated Alkenes to Difluoromethylated Oxindoles. Issue 22 (14th July 2016) - Wang, Xinglu; Wan, Wen; Chen, Yunrong; Li, Jialiang; Jiang, Haizhen; Wang, Yong; Deng, Hongmei; Hao, Jian
Abstract : A simple Ag I ‐mediated direct difluoromethylation reaction of activated alkenes by using TMSCF2 COOEt (TMS = trimethylsilyl) under mild reaction conditions has been described. This reaction tolerates a variety of functional groups and allows for a highly efficient synthesis of various difluoro‐containing oxindoles. Mechanistic investigations indicate that a difluoromethyl radical initiated the cascade sequence by undergoing an addition reaction to the alkene. Abstract : A highly efficient synthesis of various difluoro‐containing oxindoles has been achieved by using the described Ag I ‐mediated direct difluoromethylation reaction of activated alkenes.